Strain‐Induced Structure Evolution of Multimetallic Nanoplates. (30th July 2022) - Mahmood, Azhar; He, Dequan; Talib, Shamraiz Hussain; He, Ying; Song, Zhongqian; Zhenbang, Liu; Han, Dongxue; Niu, Li
Abstract: The surface structure and lattice strain necessary  to optimize oxygen reduction reaction (ORR) in a cost‐effective electrocatalyst still requires systematic exploration. Here, by means of oxidative etching of surface confinement stacking faults, a comparative study of the influence of defects on the growth and lattice strain of PtAgPb core‐shell nanoplates for ORR is conducted. Stacking faults are key to forming the core–shell structure and induce tensile and compressive strains to improve catalytic performance of nanoplates. In particular, the compressive strain arising from the optimal composition of nanoplates enhances the ORR activity. The findings show how compressive strain in core–shell nanoplates shift the electronic band structure of platinum (Pt) and weakens chemisorption of oxygenated species. As a result, the obtained PtAgPb‐IV/C nanoplates display superior specific and mass activities (5.06 mA cm −2 and 2.24 A mgPt −1 ) for ORR that are ≈18 and ≈13 times higher than that of commercial Pt/C, placing it among the best reported Pt based ORR electrocatalysts. Furthermore, the PtAgPb‐IV/C catalyst exhibits substantially improved durability relative to commercial Pt/C catalysts. This work represents a major step toward the deterministic synthesis of Pt‐based multimetallic nanocrystals with specific structure and surface strain for efficient ORR performance. Abstract : By oxidative etching of surface confinement defects, the solid nanoplates (PtAgPb‐I) switched to core–shell nanoplates (PtAgPb‐IV), which generate compressive surface strain in PtAgPb‐IV and enhance oxygen reduction reaction (ORR). In detail, PtAgPb‐IV/C exhibits superior specific and mass activities (5.06 mA cm −2 and 2.24 A mg −1 Pt ).